2021
DOI: 10.3168/jds.2020-19189
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood calcium concentration in the first 3 days after parturition and energy balance metabolites at day 3 in milk with disease and production outcomes in multiparous Jersey cows

Abstract: Research exploring specific associations of markers of negative energy balance and Ca in postpartum Jersey cows with lactation performance is lacking. Our objectives were to evaluate the associations of total Ca concentration (tCa) measured at 1 through 3 d in milk (DIM) and free fatty acids (FFA), β-hydroxybutyrate (BHB), and glucose measured at 3 DIM with (1) the risk of multiparous Jersey cows being diagnosed with early-lactation diseases and culling, (2) milk production in the first 9 wk of lactation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
1
11
1
Order By: Relevance
“…The same optimal threshold for serum Ca categorization and prediction of pregnancy to first service identified in our study (1.90 mmol/L within 24 h postpartum) was reported by Venjakob et al (2018). This study included 1,238 cows from 125 herds and reported a 40% decrease in the odds of pregnancy to first service for cows with (Gild et al, 2015;Gobikrushanth et al, 2020;Menta et al, 2021). Other authors have shown detrimental effects of postpartum blood Ca concentration below various thresholds on estrus cyclicity (Ribeiro et al, 2013;Rodríguez et al, 2017;Jeong et al, 2018) and number of services per pregnancy (Ribeiro et al, 2013;Braga Paiano et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The same optimal threshold for serum Ca categorization and prediction of pregnancy to first service identified in our study (1.90 mmol/L within 24 h postpartum) was reported by Venjakob et al (2018). This study included 1,238 cows from 125 herds and reported a 40% decrease in the odds of pregnancy to first service for cows with (Gild et al, 2015;Gobikrushanth et al, 2020;Menta et al, 2021). Other authors have shown detrimental effects of postpartum blood Ca concentration below various thresholds on estrus cyclicity (Ribeiro et al, 2013;Rodríguez et al, 2017;Jeong et al, 2018) and number of services per pregnancy (Ribeiro et al, 2013;Braga Paiano et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
“…Negative associations between postpartum blood Ca concentration below various thresholds and reproductive outcomes are commonly reported in Holstein cows (Caixeta et al, 2017;Umaña Sedó et al, 2018;Venjakob et al, 2018); however, Menta et al (2021) did not detect an association between postpartum plasma Ca concentration and pregnancy within 150 DIM in Jersey cows. Overall, we observed an impaired reproductive performance for cows with low serum Ca concentration shortly after calving, compared with previous research.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…A more detailed description of herd demographics, average milk production, reproductive program used, and total mixed ration offered to the close-up and fresh cows can be found in Menta et al (2021) [5]. Of note, prepartum cows were fed a negative dietary cation-anion diet.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%